Associations between Early Psychosocial Deprivation, Cognitive and Psychiatric Morbidity, and Risk-taking Behavior in Adolescence. Issue 6 (2nd November 2022) - Wade, Mark; Carroll, Devon; Fox, Nathan A.; Zeanah, Charles H.; Nelson, Charles A.
ABSTRACT: Objective: Early psychosocial deprivation increases the risk of later cognitive and psychiatric problems, but not all deprived children show these difficulties. Here, we examine the extent to which psychosocial deprivation increases the risk of later cognitive and psychiatric difficulties and the downstream consequences of this for risk-taking behavior in adolescence. Method: Children abandoned to institutions early in life were randomly assigned to care-as-usual or a foster care intervention during infancy. A separate group of never-institutionalized children was recruited as a comparison sample. The current follow-up study included 165 children (51% female), 113 with a history of institutionalization and 52 with no such history. At age 12, caregivers reported on children's psychiatric difficulties, and their IQ was assessed by standardized testing. At 16 years, risk-taking behavior was assessed from youth self-reports. Results: Latent profile analysis revealed three subgroups of children with varying levels of cognitive and psychiatric difficulties: Low-Morbidity ( n = 104, 62.7%), Medium-Morbidity ( n = 46, 27.9%), and High-Morbidity ( n = 15, 9.4%). Nearly half of the institutionalized children belonged to the High- or Medium-Morbidity subgroups; and institutionally-reared children were significantly more likely to belong to one of these profiles than never-institutionalized children. Compared to the Low-Morbidity subgroup, membership in the Medium-Morbidity profile was associated with higher levels of risk-taking behavior at age 16 years. Conclusions: Children who experience psychosocial deprivation are considerably more likely to present with elevated cognitive and psychiatric difficulties in early adolescence and, for some children, this elevation is linked to heightened risk-taking behavior in later adolescence.